2015
DOI: 10.1128/aem.00307-15
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Honey Bee Gut Microbiome throughout the Queen-Rearing Process

Abstract: The European honey bee (Apis mellifera) is used extensively to produce hive products and for crop pollination, but pervasive concerns about colony health and population decline have sparked an interest in the microbial communities that are associated with these important insects. Currently, only the microbiome of workers has been characterized, while little to nothing is known about the bacterial communities that are associated with queens, even though their health and proper function are central to colony pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
116
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 50 publications
8
116
0
1
Order By: Relevance
“…We found that honey bee larvae are colonized with Fructobacillus, Alpha-2.2, and Lactobacillales. Other studies of honey bee larvae also identified Alpha-2.2 and Lactobacilliales as early colonizers (24,44,45), suggesting that these clades may be commonly found with young, larval bees. It is important to note that these culture-based studies are dependent on the medium used to select for microbial members and that the medium used here (and in previous work) selects for acetic and lactic acid bacteria.…”
Section: Figmentioning
confidence: 87%
“…We found that honey bee larvae are colonized with Fructobacillus, Alpha-2.2, and Lactobacillales. Other studies of honey bee larvae also identified Alpha-2.2 and Lactobacilliales as early colonizers (24,44,45), suggesting that these clades may be commonly found with young, larval bees. It is important to note that these culture-based studies are dependent on the medium used to select for microbial members and that the medium used here (and in previous work) selects for acetic and lactic acid bacteria.…”
Section: Figmentioning
confidence: 87%
“…In the second experiment, we observed a large number of non-core bacteria, particularly P. apium , non-Firm 4 and Firm 5 Lactobacillus sp., Enterococcaceae , and the pathogen P. larvae . P. apium is found at lower levels in the gut (Corby-Harris et al 2014a;Martinson et al 2011;Martinson et al 2012;Moran et al 2012;Sabree et al 2012) and is typically more abundant in hive food stores (Anderson et al 2014), queens (Kapheim et al 2015;Tarpy et al 2015), larvae (Vojvodic et al 2013), and in the hypopharyngeal glands and crops of nurses (Corby-Harris et al 2014b). Because P. apium is relatively abundant in food stores, hypopharyngeal glands, and crop, one possibility is that the guts displaying high P. apium titers were recently inoculated through either pollen feeding or trophallaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller numbers of bacteria, often representing environmental species, occur in the foregut and midgut [3]. The core species are relatively infrequent in larvae and in adult queens, which contain highly variable communities dominated by environmental bacteria [4, 5]. The mature worker hindgut microbiome is substantial, totaling 10 8 –10 9 bacterial cells [6] and is established in workers within four days following eclosure, before leaving the hive.…”
Section: The Gut Microbiome Of Corbiculate Beesmentioning
confidence: 99%
“…While a largely consistent microbiome persists throughout the lifespans of honey bee adult workers, adult queens have a strikingly different microbiome composition, with greater variation among individuals, and consisting of bacteria that are also found in the hive environment [4 • ,5]. The size of the queen microbiome is highly variable but often smaller than that of workers.…”
Section: Environmental and Developmental Factors That Can Alter The Bmentioning
confidence: 99%